Quality of Service Practices within Business Market: An Automotive Industry Experience - Jamaludin Akbar; Mohd Rizaimy Shaharudin; Siti Fairuza Hassam; Nurdiyana Nazihah Zainal; Amir Imran Zainoddin (International Journal of Supply Chain Management, 2018)
In todays business market, products alone cannot assure vendors success due to the trend of the market where buyers perceived products and services are equally important. To face this current development, vendors are forced to offer added values to their products. Excellent quality of service is one of the options available because it can lead to the buyers satisfaction, and ultimately, loyalty. To date, little is known about the quality of service practices in the Malaysian Automotive Industry. Therefore, the case study was conducted to understand the practices better. It was investigated in the language of the actors in the industry specifically the buyers. In-depth interviews were conducted to explore the quality of service practices which were felt to be crucial to this study. A hermeneutics analysis method was employed in analyzing the data. Results from the case studies indicated that quality of service practices has played significant roles in the Malaysian Automotive Industry. In addition, the practices are consistent with the four main principles in a buyer-vendor relationship within the automotive industry. This is in line with the current market trend.